Influencing factors of rehabilitation participation among patients with pneumoconiosis in Chongqing, China - Xiaodong Wang; Lvsu Ye; Lijie Long; Xiaoya Huang; Yongyi Wang (Frontiers in Medicine)
BackgroundPneumoconiosis is the most serious and common occupational disease in China. This study aimed to analyze the factors influencing participation in pulmonary rehabilitation among patients with pneumoconiosis and provide a basis for decision-making to promote their engagement in rehabilitation.MethodsWe collected data from patients with complete file information between January 2020 and December 2023. The basic information, disease stage, and other characteristics were analyzed. SPSS (version 22.0) statistical software was used for the chi-square test, U-test, and logistic regression analysis.ResultsA total of 1994 patients with pneumoconiosis were included in this study. Of these, 77.8% of the patients participated in rehabilitation and 22.2% did not take part. Comparisons between the two groups revealed that the average annual hospitalization times, hospitalization expenditure, patient income, family expenditure, and disability level in the rehabilitation group were higher than in the non-rehabilitation group (p < 0.05). There were statistical differences in household nature, education level, employment status, disease stage, complications, and smoking composition (p < 0.05). Logistic regression analysis indicated that patients with urban household registration, smoking history, and complications were less likely to participate in rehabilitation. Conversely, individuals with a higher educational level, advanced disease stage, annual hospitalization expenditure and family expenditure, as well as retired patients were more likely to participate in rehabilitation.ConclusionThe participation of patients with pneumoconiosis is influenced by various factors, including their household registration nature, educational level, and disease stage. Additional measures should be taken to improve the patients’ motivation for rehabilitation.